The Predictive Value of the NEO-FFI Items: Parsing the Nature of Social Anhedonia Using the Revised Social Anhedonia Scale and the ACIPS - Gooding, Diane C.; Padrutt, Emily R.; Pflum, Madeline J. (Frontiers in Psychology, 2017)
The goal was to examine the nature of social anhedonia using two validated measures and study their relationship to scores on the NEO-FFI. Nearly nineteen hundred college-aged participants completed the Chapman revised social anhedonia scale (RSAS), Anticipatory and Consummatory Interpersonal Pleasure Scale (ACIPS), and the NEO-FFI. Although both the RSAS and ACIPS were associated with the NEO-FFI domains of Extraversion, Agreeableness, and Neuroticism, linear regression analyses revealed that the RSAS and ACIPS were differentially predicted by NEO-FFI item clusters. The RSAS scores were predicted by Sociability, Nonantagonistic Orientation, Positive Affect, and Activity item clusters. The ACIPS scores were predicted by Sociability, Prosocial Orientation, Activity, aand Positive Affect item clusters in addition to gender. In summary, it appears that social anhedonia is multidimensional, associated with various personality domains encompassing social approach and withdrawal.